1975
DOI: 10.1037/h0077164
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic mechanism for social control of fissioning in planarians: III. Central nervous system centers of facilitation and inhibition.

Abstract: Previous studies have indicated that asexual reproduction (fissioning) in the planarian Dugesia dorotocephala is socially controlled through a cephalic mechanism: Isolation releases fissioning; grouping inhibits it; decapitation, at the level of the auricles, releases it even in grouped subjects. The brain is not necessary for programming the actual events of fissioning; these are orchestrated by the segmental plexus fissioning (SPF) system. Various surgical cuts were made to ablate selected portions of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…Specimens of clonal asexual Dugesia japonica were used for all fission experiments. Since planarians do not need a brain to fission, specimen were decapitated to increase the likelihood of fission in the presence of light (34). Details on planarian maintenance, fission experiments and analysis are provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens of clonal asexual Dugesia japonica were used for all fission experiments. Since planarians do not need a brain to fission, specimen were decapitated to increase the likelihood of fission in the presence of light (34). Details on planarian maintenance, fission experiments and analysis are provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Determining which of the physiological components of the fissioning system previously elucidated in the SCD Ss 1969, 1975Pigon et al, 1974 ;Morita & Best, 1984) have been altered in the BFH Ss will require further study .…”
Section: Resultsmentioning
confidence: 99%
“…Previously published studies on fissioning of asexual Dugesia dorotocephala revealed that : its incidence is suppressed in a graduated manner by cohorts ; it is more likely in longer than shorter specimens (Ss) ; it is modulated by photoperiod ; it occurs with a high incidence in decapitated Ss, irrespective of cohorts or photoperiod (Best et al, 1969(Best et al, , 1975Pigon et al ., 1974 ;Morita & Best, 1984) . All of these previous studies were done with laboratory cultures of Ss originally collected from a pond and stream fed from outflow from the Soldier Canyon Dam (SCD) approximately 6 miles northwest of Fort Collins, Colorado .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that decapitated asexual worms show a higher rate of fission than intact worms, suggesting that the brain exerts an inhibiting control of fission (Kamatani, 1960;Best et al, 1969;Best et al, 1975;Morita, 1990). Indeed, the tail fragments from asexual worms underwent fission within a week of surgical ablation, whereas the head fragments started only began fission a month later.…”
Section: Critical Steps In Sexual Inductionmentioning
confidence: 94%